Risk Management Analysis of School Management Information Systems Using ISO 31000:2018 - Sulistiawati, Anita; Hartomo, Kristoko Dwi (Sistemasi: Jurnal Sistem Informasi, 2024)
The school management information system (SIAHDU) is an application managed by the IT department of a Vocational High School in Salatiga City. This application is an application of SI/IT in the education sector which was created with the aim of making school business processes more effective and efficient, such as administrative activities for paying tuition fees, managing grades and report cards, violation points, attendance and student biodata that can be accessed by teachers and students. With the convenience provided, it cannot be denied that risks will always arise both internally and externally. Based on this, risk management activities need to be carried out to minimize risks that might hamper and stop the system's business processes. In this research, the ISO 31000:2018 framework is used as a risk analysis assessment guide. The stages used are divided into risk assessment and mitigation stages so that it is hoped that they can minimize and overcome existing risks. The aim of this research is to carry out risk assessments and risk mitigation in school management information system applications using ISO 31000:2018. The results of the day of research that was carried out contained 25 risk opportunities, three of which were at a high level, fourteen were at a medium level, eight were at a low level. It is hoped that the results of this risk management documentation will become a reference for schools to implement new policies to minimize risk opportunities Keywords: risk management, ISO 31000:2018, risk analysis